OPTIMIZATION OF THE ROLE OF WIDYAISWARA, WIDYAPRADA, WIDYABASA AND WIDYABHAKTI COMPETENCIES IN IMPORTING THE QUALITY OF TRAINING - Nurhofipah Hutabarat; Tuti Andriani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research examines the roles, duties and competencies of various functional positions in the education and training sector, namely Widyaiswara, Widyaprada, Widyabasa and Widyabhakti. Training has an important role in improving understanding, skills and knowledge which have an impact on individual and group performance. This research uses the library study method to collect and analyze data from various relevant literature. The results of this research show that Widyaiswara focuses on implementing education and training, with competencies that include learning management, substance, personality and social. Widyaprada plays an important role in ensuring the quality of education, being responsible for improving the performance of educational units through various training programs. Widyabasa plays a role in developing, fostering and protecting language and literature, while Widyabhakti integrates community service with training to improve the quality of life of the community. Through a comprehensive approach, this journal explores how these functional positions contribute to improving the quality of education and developing human resources.